Physical education in prophetic hadith: educational perspectives for contemporary Islam - Ilham Ilham; Nurul Ihsan; Zulbahri Zulbahri; Ahmad Rivauzi (Global Econedu, 2026)
This study examines the Prophetic hadiths related to physical education and analyzes their educational significance within the framework of Islamic education. A qualitative library research approach was employed using the Kutub al-Tis‘ah, classical and contemporary hadith commentaries, and relevant scholarly literature. Data were identified through thematic hadith analysis, verified for authenticity, classified into themes, and analyzed using descriptive and content analysis. The findings indicate that physical education in the Hadith encompasses hygiene, physical fitness, sports, nutrition, disease prevention, environmental cleanliness, mental health, and healthy lifestyles. These teachings support the objectives of maqāṣid al-sharīʿah, particularly preserving life, intellect, and human dignity. Physical education is an integral component of Islamic education, providing a theoretical foundation for developing holistic curricula based on authentic Prophetic traditions.